Cell size dynamics and viability of cells exposed to hypotonic treatment and electroporation for electrofusion optimization - Ušaj, Marko (Radiology and oncology (Ljubljana), 2009)
Background. Various electrofusion parameters have to be adjusted to obtain theoptimal electrofusion efficiency. Based on published data, good electrofusion conditions can be achieved with the hypotonic treatment. However, the duration of the hypotonic treatment before electroporation and buffer hypoosmolarity have to be adjusted in order to cause cell swelling, to avoid regulatory volume decrease and to preserve cell viability. The aims of our study were to determine cell size dynamics and viability of four different cell lines in hypotonic buffer and to study the influence of the electroporation on the selected cell line in hypotonic buffer. Materials and methods. Cell size dynamics of different cell lines exposed to hypotonic buffer and electroporation were analyzed by time-resolvedcell size measurements. The viability of hypotonically treated oržand electroporated cells was determined 24 h after the experiment by a modified crystal violet (CV) viability assay. Results. In our experimental conditions the hypotonic treatment at 100 mOsm was efficient for CHO, V79 and B16-F1 cell lines. The optimal duration of the treatment was between two and five minutes. On the other hand the same hypotonic treatment did not cause cell swelling of NS1 cells. Cell swelling was also observed after electroporation of B16-F1 in isotonic buffer and it was amplified when hypotonic buffer was used. In addition, the regulatory volume decrease was successfully inhibited with electroporation. Conclusions. Cell size dynamicsin hypotonic conditions should be studied for each cell line since they differ in their sensitivity to the hypotonic treatment. The inhibition of cell regulatory volume decrease by electroporation may be beneficial in achieving higher electrofusion efficiency. (Abstract truncated at 2000 characters)
Keywords: celice; citologija; elektrofuzija; elektroporacija; fiziologija celic; hipotonični pufer; nabrekanje celic